Mean blood pressure according to the hypertension care cascade: Analysis of six national health surveys in Peru - Rodrigo M. Carrillo-Larco; Wilmer Cristobal Guzman-Vilca; Antonio Bernabe-Ortiz (Elsevier, 2021)
Background: While we have good evidence about the hypertension care cascade, we do not know the mean blood pressure (BP) in these groups. We described the mean BP in four groups based on the hypertension care cascade at the national and sub-national levels in Peru. Methods: Descriptive analysis of six national health surveys. Blood pressure was measured twice and the second record herein analysed. We defined four groups: i) people with self-reported hypertension diagnosis receiving antihypertensive medication; ii) people with self-reported hypertension diagnosis not receiving antihypertensive medication; iii) people unaware they have hypertension with blood pressure ≥140 or 90 mmHg; and iv) otherwise healthy people. Findings: There were 125,066 people; mean age was 49.8 years and there were more women (51.7%). At the national level, in men and women and throughout the study period, we observed that the mean systolic BP (SBP) was the highest in people unaware they have hypertension; the mean SBP was similar between those with and without antihypertension medication, yet slightly higher in the former group. At the sub-national level, even though the mean SBP in the unaware group was usually the highest, there were some regions and years in which the mean SBP was the highest in the untreated and treated groups. Interpretation: These results complement the hypertension care cascade with a clinically relevant parameter: mean BP. The results point where policies may be needed to secure effective interventions to control hypertension in Peru, suggesting that improving early diagnosis and treatment coverage could be priorities. Funding: Wellcome Trust (214185/Z/18/Z).